PERBEDAAN HASIL BELAJAR SISWA HAFAL PERKALIAN DAN YANG TIDAK HAFAL PERKALIAN PADA PENGERJAAN PECAHAN PECAHAN CAMPURAN KELAS V SD NEGERI 108/VI LUBUK BERINGIN - Riri Sulistia (Mat-Edukasia, 2019)
This study aims to describe the differences in learning outcomes of students who memorize multiplication and those who don't memorize multiplication on the subject of mixed fractions. The hypothesis in this study is that there are differences between the learning outcomes of students who memorize multiplication and those who don't memorize multiplication. In this study used experimental research. The sample of this research is the students of class V SD N 116 / VI Muara Siau as an experimental class as many as 23 students and students of class V SD N 108 / VI Lubuk Beringin as control classes as many as 23 students. The instrument in data collection uses essay test techniques. The results of the analysis of research data can be obtained that the mathematics learning outcomes of students who memorize multiplication are better than the mathematics learning outcomes of students who do not memorize multiplication on the 95% confidence level, the average learning outcomes and standard deviations of the two classes compared ie x = 71 , 94, sdx = 9.74 and y = 60.86, sdy = 8.36. From the hypothesis test shows that or 7.1948> 1,721 at the 95% confidence level. Based on the calculation obtained = 7.1948 and = 1.721 then Ha is accepted and Ho is rejected. This proves that the mathematics learning outcomes of students who memorize multiplication are higher than the mathematics learning outcomes of students who don't memorize multiplication.